Small Intestinal Bacterial Overgrowth (SIBO) and Twelve Groups of Related Diseases—Current State of Knowledge - Paulina Roszkowska; Emilia Klimczak; Ewa Ostrycharz; Aleksandra Rączka; Iwona Wojciechowska-Koszko; Andrzej Dybus; Yeong-Hsiang Cheng; Yu-Hsiang Yu; Szymon Mazgaj; Beata Hukowska-Szematowicz (Biomedicines, 2024)
The human gut microbiota creates a complex microbial ecosystem, characterized by its high population density, wide diversity, and complex interactions. Any imbalance of the intestinal microbiome, whether qualitative or quantitative, may have serious consequences for human health, including small intestinal bacterial overgrowth (SIBO). SIBO is defined as an increase in the number of bacteria (103–105 CFU/mL), an alteration in the bacterial composition, or both in the small intestine. The PubMed, Science Direct, Web of Science, EMBASE, and Medline databases were searched for studies on SIBO and related diseases. These diseases were divided into 12 groups: (1) gastrointestinal disorders; (2) autoimmune disease; (3) cardiovascular system disease; (4) metabolic disease; (5) endocrine disorders; (6) nephrological disorders; (7) dermatological diseases; (8) neurological diseases (9); developmental disorders; (10) mental disorders; (11) genetic diseases; and (12) gastrointestinal cancer. The purpose of this comprehensive review is to present the current state of knowledge on the relationships between SIBO and these 12 disease groups, taking into account risk factors and the causal context. This review fills the evidence gap on SIBO and presents a biological–medical approach to the problem, clearly showing the groups and diseases having a proven relationship with SIBO, as well as indicating groups within which research should continue to be expanded.